Comparison of NLR (neutrophil/lymphocyte ratio) and PLR (platelet/lymphocyte ratio) as inflammatory markers in 1st episode mania and bipolar mania: A preliminary study - Manish K. Goyal; Ram K. Solanki; Akhilesh Jain; Kuldeep S. Yadav (Indian Journal of Psychiatry)
Background: There are various factors including inflammation that have been studied in bipolar disorder. NLR (Neutrophil to lymphocyte ratio) and PLR (platelet to lymphocyte ratio) are one of them. Various psychotropic drugs can affect the inflammatory state. Aim: This study was planned to find NLR and PLR in bipolar disorder (mania) and psychotropic drug naïve 1st episode mania. Materials and Methods: Total of 120 subjects were chosen including, 40 bipolar mania, 40 drugs naïve 1st episode mania, and 40 healthy controls. The severity of mania was assessed by the Young Mania Rating Scale. Blood samples were collected in the morning hours in order to get blood counts. Results: A significantly higher values of neutrophil counts and NLR, while the significant lower values of lymphocyte counts in both 1st episode and bipolar mania compared to healthy control were observed. The first episode mania group had significantly higher neutrophil counts and NLR in comparison to bipolar mania. Conclusion: Results suggest a possible inflammatory pathophysiology of mania. Psychotropic medicines may have an anti-inflammatory effect, signified by the fact that 1st episode mania group has a greater level of inflammation in comparison to bipolar mania.